2017
DOI: 10.1021/acs.langmuir.7b01177
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Interfacially Driven Vehiculization of Corticosteroids by Pulmonary Surfactant

Abstract: Pulmonary surfactant is a crucial system to stabilize the respiratory air-liquid interface. Furthermore, pulmonary surfactant has been proposed as an effective method for targeting drugs to the lungs. However, few studies have examined in detail the mechanisms of incorporation of drugs into surfactant, the impact of the presence of drugs on pulmonary surfactant performance at the interface under physiologically meaningful conditions, or the ability of pulmonary surfactant to use the air-liquid interface to veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…With this objective, a novel set-up based on the use of Wilhelmy troughs was designed, permitting the recreation in vitro of conditions as close as possible to the diffusion of surfactant with or without carrying drugs, allergens or particles, over the respiratory surface (figure 5C). 40 Briefly, an additional trough and a second sensor are added to the device along with a paper bridge that connects the interface of the two troughs. Surfactant can be injected into one of the troughs (the donor) that would somehow mimic the upper airways at the moment of receiving a dose of exogenous surfactant or a surfactant/drug combination.…”
Section: Surfactant Biophysics In Clinical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…With this objective, a novel set-up based on the use of Wilhelmy troughs was designed, permitting the recreation in vitro of conditions as close as possible to the diffusion of surfactant with or without carrying drugs, allergens or particles, over the respiratory surface (figure 5C). 40 Briefly, an additional trough and a second sensor are added to the device along with a paper bridge that connects the interface of the two troughs. Surfactant can be injected into one of the troughs (the donor) that would somehow mimic the upper airways at the moment of receiving a dose of exogenous surfactant or a surfactant/drug combination.…”
Section: Surfactant Biophysics In Clinical Researchmentioning
confidence: 99%
“…(B) In vitro protocols to study the inhibition by serum in the Wilhelmy trough and the captive bubble surfactometer (CBS). (C) Double balance set-up to recreate PS and PS/drug spreading along the air-liquid interface, mimicking in vitro surfactant distribution from upper to lower airways (modified from 40).…”
Section: Surfactant Biophysics In Clinical Researchmentioning
confidence: 99%
“…The feasibility of delivering nebulized surfactant during Continuous Positive Airway Pressure (CPAP) ventilation has also been addressed in several clinical studies [14][15][16][17][18], in the search for a truly non-invasive surfactant delivery method that could avoid intubation. Eventually, nebulized surfactant could also enable the co-delivery of other drug molecules, which would significantly benefit from the intrapulmonary spreading properties of exogenous surfactant [19,20]. Clinical studies with nebulized surfactant during CPAP have demonstrated the safety of this surfactant delivery method; nevertheless, its efficacy in preterm infants with severe RDS remains uncertain due to the low lung deposition rates observed in this patient population [21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the intratracheal instillation of corticosteroids combined with surfactant to prevent and/or treat BPD has become a new option. Studies have demonstrated that the intratracheal administration of surfactant and corticosteroid mixtures might synergistically improve lung function, thereby reducing the incidence of BPD because pulmonary surfactants can decrease surface tension, and surface tension gradients facilitate corticosteroid distribution to the periphery of the lungs . In addition, surfactants may enhance the solubility of corticosteroids and increase corticosteroid absorption .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no difference was found in the long-term effects of IAC on growth in the infants with BPD. These findings may be related to the short duration and relatively small dosage of corticosteroids, but further research is 43 In addition, surfactants may enhance the solubility of corticosteroids and increase corticosteroid absorption. 44 However, corticosteroids may increase the synthesis of surfactants and the gene transcription of the surfactant proteins SP-A and SP-B.…”
Section: Main Findingsmentioning
confidence: 98%